Mutations in RARS cause hypomyelination. Issue 1 (16th May 2014) - Wolf, Nicole I.; Salomons, Gajja S.; Rodenburg, Richard J.; Pouwels, Petra J. W.; Schieving, Jolanda H.; Derks, Terry G. J.; Fock, Johanna M.; Rump, Patrick; van Beek, Daphne M.; van der Knaap, Marjo S.; Waisfisz, Quinten
<x xml:space="preserve">Abstract</x> Hypomyelinating disorders of the central nervous system are still a diagnostic challenge, as many patients remain without genetic diagnosis. Using magnetic resonance imaging (MRI) pattern recognition and whole exome sequencing, we could ascertain compound heterozygous mutations in RARS in 4 patients with hypomyelination. Clinical features included severe spasticity and nystagmus. RARS encodes the cytoplasmic arginyl‐tRNA synthetase, an enzyme essential for RNA translation. This protein is among the subunits of the multisynthetase complex, which emerges as a key player in myelination. Ann Neurol 2014;76:134–139